First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations average of one week lost for each worker. The steps he advocated included the encouragement of a "will to health" in the people and a recognition by each citizen of individual responsibility. It was wrong to be ill if illness was avoidable. Mrs. SCHARLIEB referred to the war's effect on the home and on the infant — the impaired physique, particularly of the nervous system, which the men have brought back and the effects of this. Mr. E.B. TURNER dealt with the "greatest killing diseases" — excess in alcohol, tuberculosis, and syphilis. The rockbottom, in his view, was bad, overcrowded, insanitary houses. After 40 years' work among people well clothed, well housed, and well fed, he had seen only three cases of consumption — tubercle of the lungs. People crowded in small houses, herded together, men and women in one room, could not be moral. They were not immoral, but unmoral. Miss OLGA NETHERSOLE, the hon. organiser and original founder of the League, described the shame with which she saw the conditions in London slums. She referred to the "waste of prostitution," and urged reform of the bastardy and divorce laws and the creation of pensions for unsupported mothers. Reprinted from the DAILY TELEGRAPH, May 25th 1921. THE NATION'S HEALTH. APPEAL FOR £100,000. An appeal to the public for an endowment fund of £100,000 for the People's League of Health was launched on Empire Day, 1921, at a reception given by the Marchioness Curzon of Kedleston, held at 1, Carlton House Terrace. Sir BRUCE BRUCE-PORTER, representing the medical council of the League, said there was an extremely fine harvest waiting for the People's League of Health if they only had the help they deserved. Until the war there was never any attempt, of a systematic character, to find out what the health and conditions of the people of this country were. When the investigation was made, a lamentable state of affairs was revealed. There was an appalling number of C3 men. The call to put matters right did not end with the war. We wanted a far finer population for the industrial fight that had to go on if this Empire was not to go bankrupt. We could not have efficiency and bad health. Ill-health bred discontent. The working man had to fight for his bread and butter, and he was no exception to other people. RESPONSIBILITIES OF WEALTH. In other countries, particularly in America, millionaire business men gave big sums of money to all sorts of things in connection with health. They realised that their workmen were the most important and valuable piece of their machinery, and they did all sorts of things to keep them efficient. The old rich, now very largely numbered among the new poor, gave as no other people in any country gave. But the money spent in the war had not gone to the bottom of the sea: it had gone into other pockets. Those people must be taught something of the responsibilities that went with wealth; taught to give money, and to give it to the People's League of Health for the benefit of those less fortunate than themselves. One of the great aims of the League, he proceeded, was to teach people to take care of their own bodies. It was staggering to think of the ignorance there was on this subject. People knew more about their motor-cars. They trusted their children to a maid because she was nice-looking and clean, but would they trust their car to a "nice-looking, clean man"? No! They would want to know something more about him. Conditions which existed to-day were a disgrace to any community. NEGLECTED MATERIAL. The BISHOP OF BIRMINGHAM said more and more the religious teachers of this country were beginning to realise that they had to care for the healthy body of the individual as well as for his soul. Why should not an address such as Sir BRUCE BRUCE-PORTER had given be delivered in the nave of every church up and down the country? (Hear, hear.) The League of Health had an important part to play for the welfare of the future generation. There was great ignorance on the part of parents concerning the treatment of children. Ignorant affection was often more dangerous than mere coldness. Many of the young men and women of to-day, in consequence of habits bred in war-time, were not fit to be parents. These young people should be dealt with. The clergy suffered from want of knowledge in dealing with matters of public health. No man should take orders who was ignorant of how to deal with some of the terrible things he saw around him, and when he could speak with knowledge he would be listened to, even 46 200/B/3/2/C693/1/71